ARTI PENTING KEBERADAAN COVERNOTE DALAM MEMPERCEPAT PROSES PENCAIRAN KREDIT DI PT.BANK MEGA,TBK CABANG SLAMET RIYADI SURAKARTA - , yosephine minar juang sintawati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to address issues regarding the use covernote practices in accelerating the process of loan disbursement and legal effect issued by the notary covernote in speeding up the disbursement process in terms of the law of treaties and the law notary. This study juridical emphasis on empirical field research related to the issuance covernote with primary data source based on the direct study of the covernote used to obtain data directly from the source. Data obtained both secondary data and primary data processed qualitatively and then presented descriptively with the outlines and describes in accordance with the problems associated with the research findings. The results showed that: (1) the use of practice issued by the notary covernote in speeding up the process of withdrawal of credit is based on the general policy of the bank (Best Practices) which allows the credit to be drawn by the debtor after the receipt covernote without waiting for the completion of a copy of the deed, (2) the notary Covernote not have the force of law as ambtelijke acte, so it does not have the force of law is perfect, but only has the strength of evidence as evidence or clues kea direction can be used as additional evidence, and entirely dependent on the judge's assessment as provided for in paragraph 2 of Article 1881 Civil Code. When viewed in terms of the law of treaties, has the power of law covernote for both parties that should be done consistently if covernote requirements are listed in the credit agreement that was made legally. An examination of the law notary covernote unregulated Notary Act (UUJN) so that the impact of general law applicable both civil and criminal.